26.4k views
19 votes
If a = 2, b = 3 and c = 4, what is the numerical value of the expression (b-c)^2 + a(b+c)?

User Kjaquier
by
4.9k points

2 Answers

11 votes

Answer:

  • 15

Explanation:

We know that:

  • Given expression:
    (b-c)^2 + a(b+c)
  • a = 2
  • b = 3
  • c = 4

Solution:


  • (b-c)^2 + a(b+c)
  • =>
    (3-4)^2 + 2(3+4)
  • =>
    (-1)^2 + 2(7)
  • =>
    [-1(-1)] + 2(7)
  • =>
    1 + 14
  • =>
    15
User Qwertyboy
by
5.0k points
10 votes

Answer:

15

Explanation:

(3 - 4)^2 + 2(3 + 4)

(-1)^2 + 2(7)

1 + 14

15

User Alex Brown
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.